2010
DOI: 10.1007/s10532-010-9341-4
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrolysis of benzonitrile herbicides by soil actinobacteria and metabolite toxicity

Abstract: The soil actinobacteria Rhodococcus rhodochrous PA-34, Rhodococcus sp. NDB 1165 and Nocardia globerula NHB-2 grown in the presence of isobutyronitrile exhibited nitrilase activities towards benzonitrile (approx. 1.1-1.9 U mg(-1) dry cell weight). The resting cell suspensions eliminated benzonitrile and the benzonitrile analogues chloroxynil (3,5-dichloro-4-hydroxybenzonitrile), bromoxynil (3,5-dibromo-4-hydroxybenzonitrile) and ioxynil (3,5-diiodo-4-hydroxybenzonitrile) (0.5 mM each) from reaction mixtures at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…Although most nitriles are highly toxic, mutagenic, and carcinogenic due to their cyano group, enzymatic hydrolysis of these compounds is a recognized method to avail a broad spectrum of useful amides, carboxylic acids, and so on [13,15]. Meanwhile, bioremediation with nitrile-converting enzymes is an efficient method for degrading highly toxic nitriles in environmental wastes and contaminants [16,17]. Nitrile catabolism comprises two distinct pathways [18]: (1) nitrilases (EC 3.5.5.1) directly convert nitriles to corresponding carboxylic acids and NH 3 ; and (2) nitrile hydratases (NHases; EC 4.2.1.84) catalyze the formation of corresponding amides from nitriles, and amidases (EC 3.5.1.4) subsequently hydrolyze amides to carboxylic acids and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most nitriles are highly toxic, mutagenic, and carcinogenic due to their cyano group, enzymatic hydrolysis of these compounds is a recognized method to avail a broad spectrum of useful amides, carboxylic acids, and so on [13,15]. Meanwhile, bioremediation with nitrile-converting enzymes is an efficient method for degrading highly toxic nitriles in environmental wastes and contaminants [16,17]. Nitrile catabolism comprises two distinct pathways [18]: (1) nitrilases (EC 3.5.5.1) directly convert nitriles to corresponding carboxylic acids and NH 3 ; and (2) nitrile hydratases (NHases; EC 4.2.1.84) catalyze the formation of corresponding amides from nitriles, and amidases (EC 3.5.1.4) subsequently hydrolyze amides to carboxylic acids and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The bioremediation potential of nitrilase has been illustrated in detail to degrade the compounds into harmless intermediates or, ultimately, carbon dioxide, as well as H 2 O. Several microorganisms are involved in the degradation of nitriles in literature [13,16,17,156]. Zhou et al reported that sodium alginate immobilized the microbial cells, which were isolated from acrylic fiber production wastewater and can degrade more than 80% of succinonitrile at the initial concentration of even 5,000 mg·L -1 after 24 h [156].…”
Section: Introductionmentioning
confidence: 99%
“…N1 in liquid medium also followed first-order kinetics, and the degradation rate decreased as the substrate concentrations increased from 50 mg/l to 100 mg/l10. Additionally, some researchers have reported that bacterial strains from the same genus Rhodococcus with the isolate MET used in this study could degrade other herbicides1718. Xiong et al 19.…”
Section: Resultsmentioning
confidence: 55%
“…NDB 1165 22b were grown in the presence of isobutyronitrile (nitrilase inducer) as described previously. 30 F. solani O1 was maintained at 4°C on a modified Czapek-Dox agar 31 and grown in the presence of 2-cyanopyridine (nitrilase inducer) as described previously. 32 …”
Section: Microorganisms and Culturesmentioning
confidence: 99%